2015
DOI: 10.1016/j.trsl.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a complex lung disease of unknown etiology. Development of IPF is influenced by both genetic and environmental factors. Recent work by our and other groups has identified strong genetic predisposition factors for the development of pulmonary fibrosis while cigarette smoke remains the most strongly associated environmental exposure risk factor. Gene expression profiling studies of IPF lung have taught us quite a bit about the biology of this fatal disease and those in peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 156 publications
(143 reference statements)
0
89
0
1
Order By: Relevance
“…Recent experimental evidence has emerged that DNA methylation is an important mechanism involved in IPF [110][111][112]. A comparative analysis of global DNA methylation examining 27 578 CpG islands combined with gene expression patterns from IPF and normal samples revealed that both DNA methylation and expression profiles were altered in IPF [113].…”
Section: Biomarkers In Ipf and Osamentioning
confidence: 99%
“…Recent experimental evidence has emerged that DNA methylation is an important mechanism involved in IPF [110][111][112]. A comparative analysis of global DNA methylation examining 27 578 CpG islands combined with gene expression patterns from IPF and normal samples revealed that both DNA methylation and expression profiles were altered in IPF [113].…”
Section: Biomarkers In Ipf and Osamentioning
confidence: 99%
“…In aggregate, these studies have consistently identified genes associated with ECM formation, degradation, signaling, smooth muscle markers, growth factors, developmental pathways, immunoglobulins, complement, and chemokines (4). The influence of cigarette smoking (5) and the dynamic gene expression changes (4) identified in IPF suggest that epigenetic mechanisms may influence the development of this disease (6). Early studies have demonstrated a link between exposure to tobacco smoke and lung cancer via methylation of CpG islands in cancer genes, such as p16 (7).…”
mentioning
confidence: 99%
“…Downregulated miRNAs in IPF lungs include let-7d, miR-29 and the miR-200 family, while upregulated miRNAs include miR-155, miR-21, miR-199 and miR-154 [126,127].…”
Section: Epigenetic Biomarkers (Micrornas)mentioning
confidence: 99%